Learn R programming - Wilkins, David (Packt, 2017)
"R is a high-level statistical language and is widely used among statisticians and data miners to develop statistical applications. This solution-based video will be your guide, taking you through different programming aspects with R. Beginning with the basics of R programming, this video provides step-by-step resources and time-saving methods to help you solve programming problems efficiently. Starting with the installation of R, each recipe addresses a specific problem with a discussion that explains the solution and offers insight into how it works. You will learn to work with powerful R tools and techniques. You'll be able to boost your productivity with the most popular R packages and tackle data structures such as matrices, lists, and factors. You'll see how to create vectors, handle variables, and perform other core functions. You'll be able to tackle issues with data input/output and will learn to work with strings and dates. Moving forward, we'll look into more advanced concepts such as metaprogramming with R and functional programming. Finally, you'll learn to tackle issues while working with databases and data manipulation."--Resource description page
Title from title screen (viewed September 19, 2017). - Date of publication from resource description page
Keywords: R (Computer program language); Machine learning; Information visualization; R (Langage de programmation); Apprentissage automatique; Visualisation de l'information; Electronic videos